A Study of Post‐Sunset Spread‐F Initiation During the 2013 EVEX Campaign. Issue 5 (29th April 2022) - Kudeki, Erhan; Reyes, Pablo; Wallace, Aaron; Ye, Bingqian; Pfaff, Robert F.; Larsen, Miguel F.; Groves, Keith M.
Abstract: Equatorial Vortex Experiment (EVEX), the EVEX mission of May 2013, carried out from Roi‐Namur, Kwajalein Atoll, explored the initiation physics of equatorial spread‐F with a pair of rockets launched simultaneously during local sunset to apogees of 182 and 331 km, respectively. EVEX measurements presented in this paper establish the existence of a differential zonal flow between plasma and neutrals at bottom‐side F‐region heights during the sunset time in support of a post‐sunset spread‐F initiation mechanism described in Kudeki et al. (2007) that is characterized by large growth rates for oblique‐propagating 10's‐of‐km‐scale electron density perturbations. F‐region plasma drifts were measured in situ using an electric field double‐probe instrument while neutral winds were measured by triangulating drifting vapor clouds. The state of the ionosphere and spread‐F irregularities were monitored by ground based ARPA Long‐Range Tracking and Instrumentation Radar and Illinois Radar Interferometer System radars using incoherent and coherent scatter techniques, respectively, as well as an ionosonde. Plain Language Summary: Understanding how the upper atmosphere and ionosphere vary with altitude at low latitudes represent a long standing goal of the space physics community. Importantly, how the motions of atmospheric and ionospheric gases change with altitude and local time at sunset at low latitudes is believed to be the key to understanding why the subsequent night‐time low‐latitude ionosphere becomes unstable. Using two simultaneous sounding rockets, a satellite pass, ground based radars, and an ionosonde, we show evidence for a vortex‐like pattern of the ionospheric motion at sunset, as well as shears in upper atmosphere motions or winds. We also provide key evidence from the measurements for the generation of post‐sunset disturbances and plasma depletions in the equatorial ionosphere caused by differential flows of the neutral and ionized gases during the sunset period. Key Points: Radar backscatter observations monitor the ionospheric density irregularities developing in pre‐ and post‐sunset equatorial E and F regions Two rockets launched into the equatorial ionosphere at sunset collect measurements of E‐ and F‐region plasma drifts and neutral winds Links between the generation of post‐sunset F‐region turbulence and sunset time F‐region winds within the plasma drift vortex are examined